Opuntia robusta mucilage combined with alginate as encapsulation matrix for Lactiplantibacillus plantarum - María de Lourdes Reyes Escogido; Daniela Barrón Vilchis; Lisset Guadalupe Zavala Martínez; Fabiola Angulo Romero (CyTA - Journal of Food, 2023)
ABSTRACTThere is a constant search for novel and inexpensive materials for the encapsulation of cells. The present study aimed to evaluate the efficiency of mucilage from young cladodes of Opuntia robusta in the encapsulation of Lactiplantibacillus plantarum 1449. The mucilage was mixed with alginate at ratios of 2:1, 1:1, and 1:2 (alginate:mucilage, AM). The mixtures were used to encapsulate L. plantarum 1449. The microcapsules were characterized by size, weight, shape, color, and stability. The results showed that increased amounts of mucilage in the mixtures influenced the stability of the microcapsules, leading to an increased amount of irregular shapes and greater variability in size and weight. The AM 1:1 showed good encapsulation efficiency (96.1 ± 0.5%) and the viability of L. plantarum 1449 after three months of storage at 4°C was 77.2 ± 2.4%. In conclusion, mucilage combined with alginate has great potential as an encapsulating agent.